ACCESSIBILITY OF EDUCATIONAL SERVICES TO THE POOR IN THE NORTHERN REGION OF PENINSULAR MALAYSIA: A SOCIO-SPATIAL PERSPECTIVE - Khoo, Suet Leng; Samat, Narimah; Sirat, Morshidi (Journal of Human Capital Development (JHCD), 2016)
In development discourse, the role of education is instrumental to assist the poor to break away from the vicious cycle of poverty. As a result, equipping a nation’s citizenry with adequate education and knowledge will ensure their ability to be self-sufficient in terms of securing gainful employment and subsequently escape the vagaries of poverty. However, in both developed and developing countries alike, the supply and concentration of educational services and amenities in terms of their location, accessibility and quality tend to be biased towards urban centres as they are unevenly distributed between urban and rural settings. Concomitant to that, incidences of poverty will incline to occur and perpetuate in places and spaces that still lack such fundamental educational services and amenities. In turn, this situation will question the extent upon which a nation’s educational aspirations, learning opportunities and knowledge development initiatives are underscored by contemporary development philosophies like “Inclusive Education” as well as “Education for All.” Arguably, for a nation to be considered as fully developed, it will require equitable access of educational opportunities and fair distribution of educational amenities to citizens from all strata of society, especially the poor, deprived and marginalised regardless of location. Against this backdrop, this study aims to examine the location, concentration and distribution of education institutions vis-à-vis incidences of poverty in the Northern Region of Peninsular Malaysia. The study used Geographic Information System (GIS) and spatial analysis to map the spatial distribution and identify distribution of higher education institutions in the Northern Region of Peninsular Malaysia. The results indicated that some areas with high concentration of poor population have low accessibility to Higher Education Institutions (HEIs). The findings from this paper will contribute towards shaping pragmatic educational planning and development policies in Malaysia. Keywords: educational services, poverty, Malaysia, socio-spatial perspective